If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x+9=2x-15
We simplify the equation to the form, which is simple to understand
8x+9=2x-15
We move all terms containing x to the left and all other terms to the right.
+8x-2x=-15-9
We simplify left and right side of the equation.
+6x=-24
We divide both sides of the equation by 6 to get x.
x=-4
| onethird(6x-9)=5x+2(x+9) | | 6v*4h+2v-h=77 | | 5m+3(4)=22 | | 3a-2=19 | | -16+9x=5x+-30 | | M-3x=2x | | -5x-16=-7x+26 | | -8r=-8r-5r | | -5(x+5)=4-(-3) | | -8r=-8r-5 | | 7w-8w=-4-30 | | 10(2x-1)+5(4x+3)=-115 | | 24=5-(3-2m) | | 3x^2+63=30x | | 12y-7y+2y= | | 5-k=11-k | | 3(3)-4y=7 | | -(4y+2)-(-3y-4)=-4 | | 12x+60=13x+2 | | 8y(8+6y)=20 | | 12x-8=3x-35 | | 5x=3(x+3) | | 54x+14=43x+14 | | 7-3(2x-5)=5(3x+4)+2x | | 3x^2-6+2=26 | | 8x^2-6x=-9 | | 4x-24=3x+3 | | x-4.3=1.8 | | 12x-31=5 | | x+14=8x+56 | | 32x^2-128= | | 5(6+s)=45 |